Preparation method and application of needle coke-based carbon / carbon composite material
Through the preoxidation and pre-carbonization treatment of needle-shaped coke-based carbon/carbon composite materials, combined with the pyrolytic carbon layer modification of phenolic resin, the interfacial reaction and cyclic performance problems of existing needle-shaped coke graphite anode materials are solved, and the electrochemical performance and structural stability of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202510535908.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2025-07-22
AI Technical Summary
The existing needle-shaped coke graphite anode material has problems such as reaction with the electrolyte, co-embedding of solvents, poor volume expansion and circulation performance in lithium-ion batteries, and the existing modification technology has problems such as insufficient interface bonding strength and poor amorphous carbon conductivity.
By pre-oxidizing and pre-carbonizing the needle coke, combined with the pyrolytic carbon layer modification of the phenolic resin, a needle coke-based carbon/carbon composite material is prepared, forming a pyrolytic carbon layer directly adhered to the needle coke surface, adjusting the interface stress and increasing the surface area and number of micropores, and enhancing the active site of hard carbon deintercalation lithium.
It significantly improves the electrochemical performance of carbon/carbon composites, enhances structural stability and lithium storage capabilities, extends service life, and optimizes electrochemical performance.
Smart Images

Figure CN120349190A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and particularly relates to a needle coke-based carbon / carbon composite material, a preparation method thereof, and an application thereof. Background Art
[0002] Lithium-ion batteries have become key components in devices such as mobile phones, laptops, and electric vehicles due to their high efficiency, long life, and environmental friendliness. Anode carbon materials, including carbonaceous materials (such as carbon fibers, graphene), silicon-based materials, and metal oxides, are crucial for improving battery performance and reducing costs.
[0003] Graphite materials have received much attention since their development, and currently, both natural and artificial graphite production processes are mature. Among them, artificial graphite such as needle coke is widely used. Due to its high graphitization degree, excellent electrical conductivity, and low cost, it has become an ideal alternative for anode materials. However, needle coke has a large specific surface area, which easily triggers electrode / electrolyte interfacial reactions, leading to excessive growth of the SEI film, resulting in irreversible capacity loss and attenuation of cycle performance.
[0004] Existing modification technologies mostly use amorphous carbon coating on needle coke. Although it can improve the cycle retention rate, there are still problems such as insufficient interfacial bonding strength, poor electrical conductivity of amorphous carbon, and polycyclic aromatic hydrocarbons generated by the pyrolysis of asphalt raw materials, which limit the local energy density of the electrode and cause an environmental burden.
[0005] The mainstream technology is to cover the surface of the microcrystalline carbon matrix with amorphous carbon to enhance cycle stability. Amorphous carbon can improve the uniformity and stability of the SEI film, stabilize the carbon structure on the graphite surface, reduce peeling, and inhibit abnormal lithium deintercalation and intercalation. Its raw materials include asphalt, phenolic resin, and polyimide, etc. Phenolic resin is commonly used as a polymer resin precursor in the preparation of carbon / carbon composites, which can be converted into amorphous carbon or hard graphite carbon and exhibit excellent electrochemical properties.
[0006] Although there are many studies on phenolic resin as a binder for needle coke, there is a lack of technical means for pre-oxidation and pre-carbonization treatment of needle coke during the preparation of carbon / carbon composites. Therefore, the present invention proposes a new solution, that is, to prepare a hard carbon / carbon composite material by pyrolyzing a phenolic resin precursor. The advantage of this technology is that before the high-temperature graphitization treatment of needle coke, the precursor is pre-oxidized and pre-carbonized by precisely controlling the process conditions, and needle coke is introduced to modify the phenolic resin pyrolysis carbon layer. The pre-carbonization process can increase the surface area and the number of micropores of the precursor, improve the active sites for lithium deintercalation and intercalation of hard carbon, and enhance the lithium storage capacity. Summary of the Invention
[0007] The object of the present invention is to provide a preparation method of a needle coke-based carbon / carbon composite material and its application in lithium battery anode materials, so as to solve the technical problems existing in the existing needle coke graphite anode materials, such as reactions with electrolytes, co-insertion of solvents, volume expansion, and poor cycle performance.
[0008] To this end, the present invention adopts the following technical solutions: A preparation method of a needle coke-based carbon / carbon composite material suitable for the negative electrode active material of a lithium battery, comprising the following steps: 1) Pretreatment: Take needle coke powder and soak it in 1-3 mol / L hydrochloric acid solution for 2-6 h, filter, and dry to obtain clean needle coke powder; 2) Pre-oxidation: Mix the clean needle coke powder and potassium nitrate powder evenly according to a mass ratio of 1:3-3:2, place it in a corundum crucible, and keep it warm at 200-300 °C for 1-3 h, wash, and dry to obtain a needle coke pre-oxidation precursor; 3) Pre-carbonization: Co-dissolve the needle coke pre-oxidation precursor, phenolic resin, and maleic anhydride in dichloromethane according to a mass ratio of (1-3):(2-6):1, stir well, then dry and cure at 90-100 °C. Place the cured product in the central part of a tube furnace, under nitrogen protection, heat it to 300-500 °C at a rate of 2-8 °C / min and keep it warm for 1-3 h, and naturally cool to room temperature to obtain a pre-carbonized needle coke carbon material; 4) Graphitization: Place the pre-carbonized needle coke carbon material in a graphite crucible, control the ratio of the powder volume to the volume of the graphite crucible cavity to be 1 / 3-2 / 3, under argon protection, heat it to 2700-2900 °C at a rate of 2-7 °C / min, keep it warm for 1-3 h, and naturally cool to room temperature to obtain a needle coke-based carbon / carbon composite material.
[0009] Compared with the prior art, the present invention has the following beneficial effects: In the existing carbon / carbon composite negative electrode materials of lithium-ion batteries during the manufacturing and use processes, since the carbon / carbon composite material is mainly composed of carbon elements, the components are greatly affected by temperature changes, and it is easy to ablate and oxidize in a high-temperature environment, resulting in no obvious improvement in its electrochemical performance, and high-temperature fatigue and fragmentation will occur during long-term use at high temperatures; the technical solution of the present invention deposits a layer of pyrolytic carbon on the precursor of the needle coke-based carbon material through pre-carbonization. This layer of pyrolytic carbon is directly attached to the surface of the needle coke carbon, which can significantly improve the electrochemical performance of the carbon / carbon composite material, including deflecting cracks in the interface area, adjusting the interface stress, and preventing cracks from spreading into the fiber interior; the phase interface formed during the pre-carbonization process can also play a role in load transfer, and has the effect of preventing or inhibiting the interdiffusion and chemical reaction of atoms between the carbon matrix and the matrix, which helps to enhance the structural stability of the composite material and extend its service life; in addition, the pre-carbonization process can increase the surface area and the number of micropores of the precursor, thereby enhancing the deintercalation and intercalation lithium active sites of the hard carbon and improving the lithium storage capacity, which is crucial for maintaining the stable structure and high performance of the hard carbon as the negative electrode material of a lithium-ion battery. Description of the Drawings
[0010] Figure 1 XRD patterns of the C / C composite samples obtained in Examples 1-3 and Comparative Examples of the present invention.
[0011] Figure 2 SEM images of the C / C composite samples obtained in Examples 1-3 and Comparative Examples of the present invention.
[0012] Figure 3 Cyclic voltammetry test curves of the C / C composite samples obtained in Example 2 and Comparative Example of the present invention.
[0013] Figure 4 Electrochemical performance test results of the C / C composite samples obtained in Examples 1-3 and Comparative Examples of the present invention, (a): cycling performance, (b): first charge-discharge test curve. Detailed implementation manners
[0014] The technical solution of the present invention will be further explained below with specific examples.
[0015] Example 1 (1) 10 g of needle coke raw materials were pulverized, and the powder was sieved using a 60-mesh sieve. The sieved powder was soaked in 1.5 mol / L hydrochloric acid solution for 6 h, and finally the suspension was filtered and the obtained powder was dried to obtain clean needle coke.
[0016] (2) 2 g of clean needle coke and 6 g of potassium nitrate powder were weighed and thoroughly mixed. Then the mixed powder was placed in a corundum crucible and kept at 275 °C for 1.5 h. After washing and drying the powder obtained by pre-oxidation with deionized water, a needle coke pre-oxidation precursor was obtained.
[0017] (3) 7.5 g of the needle coke pre-oxidation precursor, 15 g of phenolic resin, and 3.75 g of maleic anhydride were successively added to 15 mL of dichloromethane solvent, and stirred thoroughly for 1 hour. After the stirring was completed, it was dried at 100 °C for 6 h to fully cure the suspension. The cured product was placed in the central part of a tubular furnace, and nitrogen was used as the protective atmosphere. It was heated to 350 °C at a rate of 2.5 °C / min and kept at this temperature for 2.5 h, and then naturally cooled to room temperature to obtain a pre-carbonized needle coke carbon material.
[0018] (4) The above-obtained pre-carbonized needle coke carbon material was placed in a graphite crucible with a lid. The ratio of the powder volume to the volume of the graphite crucible cavity (loading amount) was controlled at about 1 / 3, and the graphite crucible was filled with argon. It was heated to 2500 °C at a rate of 2.5 °C / min, kept at this temperature for 2.5 h, and then naturally cooled to room temperature. The obtained graphitized powder was pulverized and sieved through a 325-mesh sieve to finally obtain a needle coke carbon / carbon composite material. It was denoted as C / C-1 composite material.
[0019] Example 2 (1) 10 g of needle coke raw material was crushed, the powder was sieved with a 60-mesh sieve, the sieved powder was soaked in a 2 mol / L hydrochloric acid solution for 4 h, and finally the suspension was filtered and the obtained powder was dried to obtain clean needle coke.
[0020] (2) Weigh 3 g of clean needle coke and 9 g of potassium nitrate powder, mix the two thoroughly, place the mixed powder in a corundum crucible and keep it at 250 °C for 2 h, wash the pre-oxidized powder with deionized water, and dry it to obtain a needle coke pre-oxidation precursor.
[0021] (3) 10 g of needle coke pre-oxidation precursor, 20 g of phenolic resin and 5 g of maleic anhydride were added to 20 mL of dichloromethane solvent in sequence and stirred for 1 hour. After stirring, the suspension was dried at 100 °C for 6 hours to fully solidify the suspension. The solidified material was placed in the center of a tube furnace, with nitrogen as the protective atmosphere, heated to 400 °C at 5 °C / min and kept at this temperature for 2 hours, and then cooled naturally to room temperature to obtain a pre-carbonized needle coke material.
[0022] (4) The pre-carbonized needle coke material obtained above was placed in a graphite crucible with a lid, the ratio of the powder volume to the volume of the graphite crucible cavity (filling amount) was controlled to be about 1 / 2, and the graphite crucible was filled with argon gas, heated to 2700 °C at 5 °C / min, kept warm for 2 h, and naturally cooled to room temperature. The graphitized powder obtained was crushed and passed through a 325-mesh sieve to finally obtain a needle coke / carbon composite material. This was recorded as C / C-2 composite material.
[0023] Example 3 (1) 10 g of needle coke raw material was crushed and the powder was sieved with a 60-mesh sieve. The sieved powder was immersed in a 2.5 mol / L hydrochloric acid solution for 2 h. Finally, the suspension was filtered and the obtained powder was dried to obtain clean needle coke.
[0024] (2) Weigh 4 g of clean needle coke and 12 g of potassium nitrate powder, mix the two thoroughly, place the mixed powder in a corundum crucible and keep it at 225 °C for 3 h, wash the pre-oxidized powder with deionized water, and dry it to obtain a needle coke pre-oxidation precursor.
[0025] (3) 12.5 g of needle coke pre-oxidation precursor, 25 g of phenolic resin and 6.25 g of maleic anhydride were added to 25 mL of dichloromethane solvent in sequence and stirred for 1 hour. After stirring, the suspension was dried at 100 °C for 6 hours to fully solidify the suspension. The solidified material was placed in the center of a tube furnace, with nitrogen as the protective atmosphere, heated to 450 °C at 7.5 °C / min and kept warm for 1.5 hours, and then cooled naturally to room temperature to obtain a pre-carbonized needle coke material.
[0026] (4) The pre-carbonized needle coke material obtained above was placed in a graphite crucible with a lid, the ratio of the powder volume to the volume of the graphite crucible cavity (filling amount) was controlled to be about 2 / 3, and the graphite crucible was filled with argon gas, heated to 2900 °C at 2.5 °C / min, kept warm for 2.5 h, and naturally cooled to room temperature. The graphitized powder obtained was crushed and passed through a 325-mesh sieve to finally obtain a needle coke / carbon composite material. This was recorded as C / C-3 composite material.
[0027] Comparative Example (1) 10 g of needle coke raw material was crushed and the powder was sieved with a 60-mesh sieve. The sieved powder was soaked in a 2 mol / L hydrochloric acid solution for 4 h. Finally, the suspension was filtered and the obtained powder was dried to obtain clean needle coke.
[0028] (2) Weigh 3 g of clean needle coke and 9 g of potassium nitrate powder, mix the two thoroughly, place the mixed powder in a corundum crucible and keep it at 250 °C for 2 h, wash the pre-oxidized powder with deionized water, and dry it to obtain a needle coke pre-oxidation precursor.
[0029] (3) Add 10 g of needle coke pre-oxidized precursor, 20 g of phenolic resin and 5 g of maleic anhydride to 20 mL of dichloromethane solvent in sequence and stir thoroughly for 1 hour. After stirring, dry at 100 °C for 6 h to fully solidify the suspension. Then, grind and crush the solidified material to obtain a black precursor powder material.
[0030] (4) The black precursor powder obtained above was placed in a graphite crucible with a lid, and the ratio of the powder volume to the volume of the graphite crucible cavity (filling amount) was controlled to be about 1 / 2. The graphite crucible was filled with argon gas, heated to 2700°C at 5°C / min, kept warm for 2 h, and naturally cooled to room temperature. The graphitized powder obtained was crushed and passed through a 325-mesh sieve to finally obtain a needle-shaped coke / carbon composite material. It was recorded as C / C-0 composite material.
[0031] Structural characterization and performance evaluation of the products obtained in Examples 1-3 and Comparative Examples: 1. Structural characterization Figure 1 XRD patterns of the C / C composite samples obtained in Examples 1-3 of the present invention and the comparative examples. For all composite samples, four diffraction characteristic peaks exist at 26.48°, 42.61°, 44.39° and 54.54°, corresponding to the (002), (100), (101) and (004) crystal planes of hexagonal carbon (JCPDS, 41-1487), respectively. And no other impurities were detected, indicating that the phenolic resin was completely converted into carbon after pre-carbonization and high-temperature graphitization. The structural parameter information such as the interlayer spacing, La, and Lc of the (002) plane of the composite materials obtained in each example and the comparative example is shown in Table 1. Compared with the C / C-0 composite material obtained without pre-carbonization treatment in the comparative example, the interlayer spacing of the C / C composite materials obtained in each example decreased. Among them, the interlayer spacing of the C / C-2 composite material obtained in Example 2 decreased to 0.3356 nm, approaching the interlayer spacing of the ideal graphite material, indicating that the material has a rich graphite microcrystalline structure, and the presence of the microcrystalline structure helps to improve the lithium insertion / extraction ability of the graphite electrode for lithium ions.
[0032] Table 1 Crystal structure information of the materials obtained in the comparative example and Examples 1, 2, and 3 Figure 2 SEM test results of the C / C composite samples obtained in Examples 1-3 of the present invention and the comparative examples. As can be seen from the figure, compared with the morphological characteristics of the composite materials obtained in the comparative example, the size of the samples obtained in each example after pre-carbonization treatment is significantly reduced, and the C / C-2 composite material in Example 2 has the best morphological characteristics, with a uniform particle size distribution.
[0033] Performance evaluation The carbon / carbon composites presented in Examples 1 to 3 and the comparative examples of the present invention were used as the negative electrode active material, and a CR2032 type button half-cell was used to test and evaluate the electrochemical performance of this active material. Specifically, the active materials prepared in Examples 1 to 3 and the comparative examples, conductive carbon black (Super P), and sodium carboxymethyl cellulose (CMC-Na) were sufficiently ground and mixed at a mass ratio of 7:2:1 to form a black slurry with a certain viscosity. Then, the slurry was evenly coated on the rough side of a metal copper foil current collector, and the copper foil with the slurry coating was placed in a vacuum drying oven and dried at 60 °C for 18 h. A MSK-T10 type electrode sheet cutting machine was used to cut the coated copper foil into circular electrode sheets with a diameter of 12 mm. A lithium metal sheet was used as the positive electrode material, a mixed solution of 1 mol / L LiPF6 (additives including EC, DEC, DMC, and their volume ratio was 1:1:1) was used as the electrolyte, and a polypropylene (PP) microporous membrane was used as the separator. A half-cell was assembled in a glove box filled with argon with the contents of H2O and O2 both less than 0.1 ppm. A CT-4000Tn type battery tester produced by Shenzhen Neware Electronic Co., Ltd. was used to perform constant current charge and discharge tests on the battery. Test conditions: room temperature 25 °C, atmospheric environment, charge and discharge voltage range of 0.01~2 V, and cyclic charge and discharge 50 times at a current density of 200 mA / g.
[0034] Figure 3 This is a cyclic voltammetry curve test result diagram of the C / C composite material samples obtained in Example 2 of the present invention and the comparative example. It can be seen that the negative electrode material obtained by the method of the comparative example without pre-carbonization treatment showed an obvious polarization reaction near the lithium insertion / extraction potential, indicating that the reversibility of the electrochemical reaction of this material was poor. On the contrary, for the negative electrode material obtained by the example after pre-carbonization treatment, the polarization phenomenon near the lithium insertion / extraction potential was significantly improved, indicating that pre-carbonization can significantly improve the microstructure inside the carbon material and thus optimize its lithium storage performance. Among them, the cyclic voltammetry curve of the C / C-2 negative electrode material obtained in Example 2 showed a high degree of coincidence near the lithium insertion / extraction potential, and almost no electrochemical polarization reaction phenomenon occurred.
[0035] Figure 4 This is a cyclic performance test result diagram of the C / C composite material samples obtained in Examples 1 to 3 and the comparative example of the present invention. It can be seen from the figure that the negative electrode material obtained without pre-carbonization treatment showed the worst cyclic performance. After the C / C-2 negative electrode material obtained in Example 2 was cycled 50 times at a current density of 200 mA / g, its electrochemical performance remained at 352.6 mAh / g, and the Coulomb efficiency was almost close to 100%. Through the above analysis, it can be seen that the technical solution provided in Example 2 is the process flow and parameters for synthesizing the C / C composite negative electrode material with the optimal electrical performance.
[0036] Although the above embodiments have described the present invention in detail, they are only a part of the embodiments of the present invention, rather than all embodiments. Other embodiments can be obtained based on these embodiments without creative efforts, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A preparation method of a needle coke-based carbon / carbon composite material, characterized in that, The following steps are involved: 1) Pretreatment: Soak the needle coke powder in 1~3 mol / L hydrochloric acid solution for 2~6 hours, filter and dry to obtain clean needle coke powder; 2) Pre-oxidation: clean needle coke powder is mixed with potassium nitrate powder, placed in a corundum crucible and kept at 200-300°C for 1-3h, washed and dried to obtain a needle coke pre-oxidation precursor; 3) Pre-carbonization: The needle coke pre-oxidation precursor, phenolic resin and maleic anhydride are dissolved in dichloromethane, fully stirred, and then dried and solidified at 90-100°C. The solidified material is placed in the center of a tube furnace, heated to 300-500°C at 2-8°C / min under nitrogen protection and kept warm for 1-3 h, and naturally cooled to room temperature to obtain a pre-carbonized needle coke material; 4) Graphitization: The pre-carbonized needle coke material is placed in a graphite crucible, heated to 2700-2900°C at 2-7°C / min under argon protection, kept warm for 1-3 hours, and naturally cooled to room temperature to obtain a needle coke-based carbon / carbon composite material.
2. The preparation method of a needle coke-based carbon / carbon composite material according to claim 1, characterized in that, In step 2), the mass ratio of the clean needle coke powder to the potassium nitrate powder is 1:3 to 3:
2.
3. The preparation method of a needle coke-based carbon / carbon composite material according to claim 1, characterized in that, In step 3), the mass ratio of the needle coke pre-oxidation precursor, the phenolic resin and the maleic anhydride is (1-3):(2-6):
1.
4. The preparation method of a needle coke-based carbon / carbon composite material according to claim 1, characterized in that, In step 4), the amount of pre-carbonized needle coke material added is controlled to be 1 / 3-2 / 3 of the volume of the graphite crucible cavity.
5. Use of the needle-shaped coke-based carbon / carbon composite material prepared by the method as claimed in claim 1 as a negative electrode active material in a negative electrode of a lithium battery.